Preparing authors, publishers and librarians to work together building open access digital libraries - Babini, Dominique (INASP, 2021)
Providing web access to full-texts and e-publications has dramatically changed the way research results are communicated and used for research, teaching, study and policy within developing regions. Building collaboration between the authors, the publishers and the librarian communities can provide innovative solutions to online publication and dissemination. Within Latin America and the Caribbean the CLACSO social sciences academic network is using a digital library model to provide a publishing platform for its member journals.